Smartphone-assisted guided self-help cognitive behavioral therapy for young people with distressing voices (SmartVoices): study protocol for a randomized controlled trial - Marialuisa Cavelti; Janko M. Kaeser; Stefan Lerch; Stephanie Bauer; Markus Moessner; Thomas Berger; Mark Hayward; Michael Kaess (Trials, 2022)
Abstract Background The long-standing view that auditory verbal hallucinations (AVH) or hearing voices is a sign of schizophrenia has been challenged by research demonstrating that they lie on a continuum ranging from normal to pathological experience related to distress and need for care. Hearing voices is more prevalent in adolescence than in later life, and hearing voices during adolescence indicates a risk for severe psychopathology, functional impairments, and suicide later in life. While there is increasing evidence for the efficacy of cognitive behavioral therapy for voices (CBTv) in adults with schizophrenia, research on psychological treatments for youth with distressing voices has been scarce. The aim of the current study is to examine the efficacy of CBTv, delivered using smartphone-based Ecological Momentary Assessment Intervention (EMI) in a transdiagnostic sample of youth. Methods This is a superiority randomized controlled trial comparing 8 weeks of CBTv-based EMI in addition to treatment as usual (TAU) versus TAU only. TAU covers both no treatment and any form of psychiatric/psychological treatment. In the EMI condition, participants will be prompted twice a day to complete an EMA survey, and receive one intervention proposal per assessment. One-hundred fifty-four youth aged 14–25 years with distressing voices will be recruited from psychiatric clinics, local private practices, internet forums, and advertisements in print and social media. Before and after the intervention phase, participants will undergo a 9-day EMA. Single-blinded assessments will be conducted at baseline (T0) and at 3-month (T1) and 6-month (T2) follow-up. The primary outcome is the distress dimension of the Auditory Hallucinations subscale of the Psychotic Symptom Rating Scales at T1. Secondary outcomes include perceived hostile intention, power, and dominance of voices, passive, aggressive, and assertive relating to voices, and negative core beliefs about the self. Discussion Adolescence provides a crucial window of opportunity for early intervention for hearing voices. However, youth are notoriously reluctant help-seekers. This study offers a low-intensity psychological intervention for youth with distressing voices beyond diagnostic boundaries that, using a mobile technology approach, may match the treatment preferences of the generation of “digital natives.” Trial registration German Clinical Trials Register DRKS00026243. Registered on 2 September 2021